Exhibiting the Exotic, Simulating the Sacred: Tibetan Shrines at British and American Museums - Imogen Clark (Ateliers d'Anthropologie)
Tibetan material culture has often been displayed in museums in the form of shrines. In these displays, Tibetan culture has been defined for viewers as overridingly religious, that is to say Buddhist. Why have shrine displays become such popular curatorial strategies? What effects do they achieve compared to “artistic” forms of representation? Why have Tibetan artefacts been predominantly constructed and displayed according to this religious vision?Paying close attention to how such displays encourage “ways of seeing” (Alpers, 1991), this paper investigates how Tibetan culture is characterised for visitors to museums. It explores the tension between “secular” and “religious” in shrine installations, and questions the relevance of these concepts for Tibetan material culture. Finally, it asks how appropriate shrine displays are according to Tibetan and Tibetan Buddhist perspectives, exploring the wider effects of these displays in relation to their representation of Tibetanness.